2011
DOI: 10.1016/j.preghy.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the primary outcomes that result from deficient spiral arterial modification in pregnant mice

Abstract: Pre-eclampsia, an acute complication of human pregnancy, is associated within complete physiological modification of decidual spiral arteries. This is thought to promote oxidative stress from perfusion/reperfusion of the placenta and to restrict placental and fetal growth. Alymphoid (genotype Rag2 −/− /Il2rg −/− ) mice, sufficient in dendritic and myeloid cell functions, lack spiral arterial modification with individual spiral arteries having ~1.7x the vascular resistance and 0.66x the blood velocity of +/+ mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…NK + T + B + ) and alymphoid (deficient in NK, T and B cells (NK − T − B − )) BALB/c-Rag2 −/− / Il2rg −/− mice before, across and after pregnancy using micro-ultrasound. Unlike most patients with impaired SA remodeling, 24 Rag2 −/− /Il2rg −/− dams with unmodified SA have normotensive pregnancies without detectable elevation in hypoxia of placental, fetal or maternal tissue. 25 They also show no elevation in fetal loss and their offspring are not growth impaired.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…NK + T + B + ) and alymphoid (deficient in NK, T and B cells (NK − T − B − )) BALB/c-Rag2 −/− / Il2rg −/− mice before, across and after pregnancy using micro-ultrasound. Unlike most patients with impaired SA remodeling, 24 Rag2 −/− /Il2rg −/− dams with unmodified SA have normotensive pregnancies without detectable elevation in hypoxia of placental, fetal or maternal tissue. 25 They also show no elevation in fetal loss and their offspring are not growth impaired.…”
Section: Introductionmentioning
confidence: 88%
“…Mean litter sizes in this study were not significantly different between genotypes. 24 All procedures were conducted under Animal Utilization Protocols approved by the Animal Care Committee, Queen's University.…”
Section: Micementioning
confidence: 99%
“…In one, blastocysts transduced with a lentiviral vector expressing hsFLT1 (an anti-angiogenic factor) the levels of hsFLT1 can be detected early in pregnancy, and gradually drive to late PE-like hypertensive and renal consequences. 6 Mouse spiral arterial remodeling is seen histologically over gestation days (gd) 10-12 of the 19-20 day pregnancy 5,7 and is a process that includes downregulation of arterial markers and acquisition of venous antigen expression. 8 Thus, spiral arterial remodeling is a mid-gestational event that coincides with the completion of placental and fetal differentiation/development and the onset of rapid fetal growth.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Recent findings, both in humans and mice, have shown that uterine NK cells are involved in endometrial remodeling, spiral artery modifications and placentation. [17][18][19][20][21] Although a large body of information on uterine NK cell function comes from data in mice, our knowledge regarding the presence and the phenotype of murine NK cells in decidua and uterus during early pregnancy (first week) is still incomplete. Another important question concerns their origin: they can be generated in situ from precursors or recruited from the periphery into decidua and uterus, where the microenvironment can modulate their phenotypic and functional characteristics.…”
Section: Introductionmentioning
confidence: 99%